A comparative study for various structures of the P-N junction on silicon (100) wafer / Mohd Ghasani Mohd Maimi. - Mohd Maimi, Mohd Ghasani (2011)
This project is to investigate the fabrication of p-n junction by using three different structures on silicon (100) wafer. A semiconductor diode is basically by made silicon material that has impurities added to it. This is to create a region on one side that contains negative charge carriers (electrons), known as n-type semiconductor, and a region on the other side that contains positive charge carriers (holes), known as p-type semiconductor. The junction's terminal attached to each region. In this project, various structures are used to compare the p-n junction characteristics and behavior for each of them. The n-type silicon wafer with orientation of (100) is used to fabricate the junction. For the impurity to obtain p-type junction, Boron dopant is used in order to produce it. This project is important to investigate the method of fabrication by using different structures of p-n junction. The fabrication process included in this project is basic fabrication process but in this project, it will concentrate on different design of the structure part. 3 sets of designed masked is needed for this project created by using Turbocad software system. The instrument that would be used during the fabrication process are wet cleaning, oxidation, photolithography, pattern transfer, wet etching, spin on dopant, diffusion and metal deposition. For the characterization part, the 4 point probe and I-V measurement would be used to obtain the electrical characteristics of the junction.